The Relation of Coordination to Verb Gapping in Biblical Poetry - Miller, Cynthia L. (Journal for the study of the Old Testament, 2007)
This essay examines the relationship between two features of biblical poetry: (1) verb gapping between lines with matching structures (i.e. identical constituents); and (2) explicit coordination of parallel lines with waw. At first glance, the presence of an explicit conjunction between such cola may appear to be optional and completely within the realm of stylistics, even though it is statistically most frequent. However, a correlation of the precise structural features of elliptical structures with the presence (and absence) of coordination suggests instead that additional syntactic and cognitive factors are at work.